2018
DOI: 10.1038/s41598-018-27516-9
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic Acid Restores Complete Transparency of Sonicated Human Cataract Ex Vivo and Delays Cataract Formation In Vivo

Abstract: Cataract, the leading cause of vision impairment worldwide, arises from abnormal aggregation of crystallin lens proteins. Presently, surgical removal is the only therapeutic approach. Recent findings have triggered renewed interest in development of non-surgical treatment alternatives. However, emerging treatments are yet to achieve full and consistent lens clearance. Here, the first ex vivo assay to screen for drug candidates that reduce human lenticular protein aggregation was developed. This assay allowed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 57 publications
0
21
1
Order By: Relevance
“…This study contains data from three cataract lenses, as it is relatively rare for a tissue donor from a first-world country to have premortem diagnosed cataracts. Previous work linked cataract formation to amyloid using lens tissue collected during surgery; however, sonication is used during cataract surgery and is known to induce amyloid formation in vitro (14). By using intact lens tissue and juvenile controls, our study provides evidence that cataracts may be an amyloid disease, akin to Alzheimer's, type 2 diabetes, and other diseases with different manifestations but all linked to amyloid formation.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This study contains data from three cataract lenses, as it is relatively rare for a tissue donor from a first-world country to have premortem diagnosed cataracts. Previous work linked cataract formation to amyloid using lens tissue collected during surgery; however, sonication is used during cataract surgery and is known to induce amyloid formation in vitro (14). By using intact lens tissue and juvenile controls, our study provides evidence that cataracts may be an amyloid disease, akin to Alzheimer's, type 2 diabetes, and other diseases with different manifestations but all linked to amyloid formation.…”
Section: Discussionmentioning
confidence: 71%
“…While it is well established that crystallins can form amyloid fibrils in vitro, there is little and conflicting evidence that human cataract tissue contains amyloid structures. Some works claim to identify amyloid structures, while others state that only amorphous aggregates occur (14,15). Some proteins form amyloid fibrils in vitro, but not in vivo, possibly reflecting that conditions used in in vitro crystallin experiments are not relevant to tissues (16).…”
mentioning
confidence: 99%
“…Our previous studies showed that both rosmarinic acid and sinapic acid had a positive effect on parameters related to glucose and lipid metabolism, as well as on some parameters of oxidative stress in the serum of ovariectomized rats in the early phase of estrogen deficiency [20,21]. Based on various experimental in vitro and in vivo animal studies, there are also suggestions on the possibility of using phenolic acids, including rosmarinic acid, to reduce cataract development [22,23,24,25]. However, there is still no data on the effects of plant-derived antioxidants, including rosmarinic and sinapic acid on oxidative stress parameters in the lenses exposed to estrogen deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…in the amplitude of a-and b-waves after insertion of rosmarinic acid-loaded implants indicates that the device or the drug released did not promote any harmful toxic effect to the retina, suggesting that it is safe for intravitreal use. Although rosmarinic acid has been previously investigated for the treatment of ocular diseases, studies demonstrating the preservation of retinal function after intravitreal injection of rosmarinic acid have not been reported [5][6][7][8][9][10]. Histopathological analysis of the retina showed the absence of inflammatory cells and hemorrhages in the areas close to the implant, as well as the integrity of the neuroretina and choroid cells (▶ Fig.…”
Section: Controlmentioning
confidence: 99%
“…Previous studies have investigated rosmarinic acid therapeutic effects in suppressing retinal and subconjunctival neovascularization, inhibiting pterygium epithelial cells, and preventing cataracts [5][6][7][8][9][10]. Diabetic retinopathy, macular edema, and age-related macular degeneration are associated with neovascularization and can cause blindness if they are not properly treated [6,11].…”
Section: Introductionmentioning
confidence: 99%